PENGARUH KEADILAN ORGANISASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MITRA TRAKTOR CAKRABUANA PEKANBARU - Putra, Anggi Pratama; Marnis, Marnis; Nuryanti, Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Research done PT. Mitra Traktor Cakrabuana Pekanbaru. The aim of the research was conducted to determine the effect of organizational justice and motivation on employee performance. The study population included all employees who totaled 43 people and set a model census. The variables used were organizational justice and motivation as independent variables, and performance as the dependent variable. Data analysis method used is descriptive analysis and multiple linear regression analysis with the help of the tool SPSS 17 for windows. The study concluded that simultaneous organizational justice and motivation significant effect on performance. The partially only motivation that shows a positive and significant effect of organizational justice while not a significant influence on employee performance. The recommendation is that the management do justice program of organizational improvement and motivation of employees, especially in terms of informationdisclosure, change management system to be participatory and to formulate the criteria and measures are transparent and fair view of the opportunities for employees to gain increasedpost.Keywords: Organizational Justice, Motivation and Performance